2019
DOI: 10.1371/journal.pone.0219342
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on Bosmina longirostris susceptibility to microcystin-LR acute toxicity

Abstract: Harmful algal blooms are an ongoing threat to many aquatic systems throughout the world. In the Chowan River, North Carolina, the frequency of toxin producing Microcystis aeruginosa blooms has increased since 1975 along with an average 0.71°C rise in water temperature. The combined effect of microcystin-LR toxin and rising temperatures on a dominant zooplankter in the system, Bosmina longirostris , was the focus of this study. Laboratory studies were conducted to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Such temperature-mediated toxicity could be responsible for the 50% decline observed in the survival of I. elegans exposed to high concentration of the crude extract at 25 °C in our study. Here, our finding supports the hypothesis on the combined effects of temperature and crude extract and corroborates earlier studies that demonstrated their combined effects on freshwater species (Kim et al 2014 ; Lamb et al 2019 ; Xiang et al 2017 ). Hence, the present study suggests that warming may co-occur with a much broad range of cyanobacterial metabolites following bloom senescence leading to impaired survival and feeding among important species (Paerl and Huisman 2008 ; Walls et al 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Such temperature-mediated toxicity could be responsible for the 50% decline observed in the survival of I. elegans exposed to high concentration of the crude extract at 25 °C in our study. Here, our finding supports the hypothesis on the combined effects of temperature and crude extract and corroborates earlier studies that demonstrated their combined effects on freshwater species (Kim et al 2014 ; Lamb et al 2019 ; Xiang et al 2017 ). Hence, the present study suggests that warming may co-occur with a much broad range of cyanobacterial metabolites following bloom senescence leading to impaired survival and feeding among important species (Paerl and Huisman 2008 ; Walls et al 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…In general, the toxicity of a range of substances such as metals (Dinh et al, 2013;Janssens, Dinh, Debecker, Bervoets, & Stoks, 2014;Sokolova & Lannig, 2008) and pesticides (Dinh, Janssens, Debecker, & Stoks, 2014a;Dinh, Janssens, & Stoks, 2016;Holmstrup et al, 2010) increases under elevated temperatures, causing synergistic effects of the stressors (Crain, Kroeker, & Halpern, 2008;Dinh et al, 2013Dinh et al, , 2014aDinh et al, , 2016Sokolova & Lannig, 2008). However, it is relatively unknown how the harmful effects of algal toxins may change under extreme temperatures (Lamb, Kimmel, & Field, 2019). This is highly relevant for two reasons.…”
mentioning
confidence: 99%
“…Firstly, the co-occurrence of warmer waters and HABs suggests that species may have to cope with both elevated temperatures and algal toxins simultaneously (Dam, 2013;Lamb et al, 2019).…”
mentioning
confidence: 99%